2016
DOI: 10.1139/cjss-2015-0139
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Tillage, Stubble Management and Nitrogen on Wheat Production and Soil Properties

Abstract: In continuous cereal-based crop rotation, inappropriate residue management such as burning and removing may deteriorate soil properties and crop productivity. The objective of this study was to evaluate the effects of different tillage systems (TSs), nitrogen fertilization, and maize (Zea mays L.) stubble management (SM) on subsequent wheat (Triticum aestivum L.) crop and soil properties. The experiment consisted of three TSs, i.e., shallowing with rotavator (0-10 cm), conventional (0-20 cm), and deep tillage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
0
19
1
Order By: Relevance
“…Pandiaraj et al (2015) pointed out that crop residue incorporation increased wheat grain yield by 1.31 times and straw yield by 1.38 times, as compared with the control without residue incorporation. Basir et al (2016) showed an increase of 12.0% and 3.5%, in wheat grain yield with residue incorporation without N application compared with the practices of removing or burning the residues. In addition, Chen et al (2018) indicated that straw incorporation increased rice and wheat grain yields by 11.6% and 11.1%, respectively, as compared with the same crops managed without residue incorporation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Pandiaraj et al (2015) pointed out that crop residue incorporation increased wheat grain yield by 1.31 times and straw yield by 1.38 times, as compared with the control without residue incorporation. Basir et al (2016) showed an increase of 12.0% and 3.5%, in wheat grain yield with residue incorporation without N application compared with the practices of removing or burning the residues. In addition, Chen et al (2018) indicated that straw incorporation increased rice and wheat grain yields by 11.6% and 11.1%, respectively, as compared with the same crops managed without residue incorporation.…”
Section: Introductionmentioning
confidence: 97%
“…Conservation agriculture and crop rotation benefit both the environment and soil fertility (Sommer et al 2007); and it has different effects on crop production and nitrogen (N) use efficiency (Limon-Ortega et al, 2004;Kazemeini et al 2014;Pandiaraj et al 2015;Basir et al 2016). Conservation agriculture can increase soil organic matter (SOM), biological activity, macroporosity, stable aggregates, water infiltration, and amount of soil water available to plant, and reduce bulk density (Fabrizzi et al 2005;Wright et al 2005;Liu et al 2014a;Basir et al 2016;Stewart et al 2018;Urra et al 2018). Formerly, Karlen et al (1994) indicated that crop rotation allowed breaking soil pathogen cycles and reduced weed pressure.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, this low NFE could also be influenced by the soil type and crop management, such as the incorporation of maize stubble, tillage, and doses of N from previous years [54]. The influence of the high soil pH (pH = 8.99) must also be highlighted, which could have been a limiting factor in the N uptake from the fertilizer and therefore could reduce the NFE, since the optimum pH for the N uptake by the crop is in a range of 6 to 7 [6].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced tillage maximizes water conservation compared to subsoiling ( Yin et al, 2021 ). Basir et al (2017) conducted tillage experiments in the wheat continuous cropping area in Pakistan and found that under the soil conditions, shallow tillage (0–0.1 m), residual mulching of maize and application of nitrogen fertilizer could improve the productivity of wheat crops. Our experiment does not involve other cultivation methods at present, only considering the effect of tillage methods on yield.…”
Section: Discussionmentioning
confidence: 99%